VERTEBRATE COMMUNITY CHANGES ACROSS A 3200M AMAZON-TO-ANDES GRADIENT: COMPOSITION, STRUCTURE, AND OCCUPANCY - Lough, Daniel (Wake Forest University, 2017)
Conservation planning depends heavily on understanding current species distributions. However, most Neotropical vertebrate distributions are poorly known and depend on field survey techniques which may not capture the full extent of an animals’ range. Here we present findings from two camera surveys in 2013 and 2016 conducted in and near Manu National Park, Peru. In 2013, 53 camera traps were installed between 3693 -1271 m a.s.l to identify both mammal and bird species along two parallel elevational transects composed of tropical montane cloud forest. In 2016, we replicated and extended the survey along one transect, setting 80 cameras from 3578 to 519 m a.s.l. We use these findings in conjunction with existing range hypotheses to assess (1) if there are major distribution changes (≥100 m, ~0.5 deg C) for mammal and bird species and whether there is a pattern among guilds and (2) quantify whether species richness across the elevational gradient changes as a result of new range estimates. Of the 83 taxa of identifiable birds, 18% had their distributions increased by ≥100 m with an average of two novel species per elevation. In contrast, of the 54 taxa of mammals detected, 44% had their distributions extended by ≥100 m, with most taxa acting as either predators or seed dispersers, with an average of six novel species per elevation sampled. These findings are crucial for expanding our understanding of tropical communities and what is needed to better conserve them.
Keywords: Camera Traps; Cloud Forest; Elevational Distributions; Granivores; Manu National Park; Seed Predation